Metropolitan ruralities - Andersson, Kjell (Professor of social sciences and rural research); Sjo<U+0308>blom, Stefan; Granberg, Leo.; Ehrstro<U+0308>m, Peter; Marsden, Terry (Bingley, U.K. : Emerald, 2016)
During modernity metropolitan ruralities have been regarded as land reserves for urban expansion. However, there is a growing insight that there are limits to the urban expansion into rural areas. Signs of a new position are the awakened interest in the nature, the authentic and the simple way of living among an urban, academically educated middle class, an actual instance of which is the interest in local food but which also is manifested in rural gentrification. However, a more hardcore turn to nature is also discernible in the renewed interest for green lungs and for eco-services more broadly. In the future, local post-fossil energy may be a main concern regarding rural eco-services utilised by urban areas. We can here imagine flows and exchanges that may demand heavy societal regulation and thus be one of the main objects of future democracy. However, despite these developments urban (and rural) policy and planning is still tightly connected to the modern expansion of the urban into the rural. There are signs of new developments and paradigm shifts but these have to be strengthened to lay the ground for rural-urban resilience.
Introduction / Kjell Andersson, Stefan Sjo<U+0308>blom, Leo Granberg, Peter Ehrstro<U+0308>m, Terry Marsden -- Neither urban nor rural: urban growth, economic functions and the use of land in the Mediterranean fringe / Luca Salvati -- The rural-urban dynamics and the Swedish-speaking Finns. Challenges and opportunities for a regionally based ethnic group / Kjell Andersson, Kenneth Nordberg, Erland Eklund -- Long wave of rural research from combating poverty to sustaining ecosystems / Leo Granberg -- Relations and areas of interaction between landowners in a peri-urban area / Ann-Sofie Richardt -- Transformation and survival strategy - rural gentrification and social sustainability in gentrified metropolitan and urban ruralities, the case of Sundom, Vaasa, Finland / Peter Ehrstro<U+0308>m -- Envisioning opportunities for agriculture in peri-urban areas / Elke Rogge -- Programme- and project-based metropolitan governance and citizen participation: a case study from the Helsinki metropolitan area / Kanerva Kuokkanen -- The prospects for bridging spatial and institutional divides within regions: rural-urban relationships in a projectified governance context / Stefan Sjo<U+0308>blom, Kjell Andersson -- Regional spatial planning, government and governance as a recipe for sustainable development? / Andrea Frank, Terry Marsden -- Exploring innovation and sustainability in the metropolitan rural areas of Budapest and Paris / Bernadett Csurgo<U+0301>, Imre Kova<U+0301>ch, Nicole Mathieu -- Urban food strategies. Exploring definitions and diffusion of European cities' latest policy trend / Agnese Cretella -- Conclusion / Kjell Andersson, Stefan Sjo<U+0308>blom, Leo Granberg, Peter Ehrstro<U+0308>m, Terry Marsden.
Includes index.
Includes bibliographical references.
Print version record
Keywords: Social Science -- Sociology -- Rural; Rural planning; Rural communities; Rural-urban relations; Rural development; City planning; Urban policy